MAURICE RAVEL: LE TOMBEAU DE COUPERIN – PART I. THE REMINISCENCE OF BAROQUE COMPOSITIONAL TECHNIQUES - OLÁH, Boglárka Eszter (Studia Universitatis Babes-Bolyai Musica, 2020)
According to Alfred Cortot, the suite Le Tombeau de Couperin could be divided into two main units: the first part presented below represents the structural arch of the suite. Each analyzed part represents a specific compositional technique of the Baroque era. The fusion between the elements of the French baroque keyboard music and the characteristics of the modern piano music transforms this piece into a real and unique masterpiece. By analyzing the Prelude, the Fugue and the Toccata we have the opportunity to understand the vision about the French baroque music created by the artists of the 20th century.